Teach yourself Visual Basic 4 in 21 days - Gurewich, Nathan; Gurewich, Ori (Indianapolis, Indiana : Sams Publishing, 1995)
Using a logical, easy-to-follow approach, this text teaches readers the fundamentals of developing programs. It starts with the basics of writing a program and then moves on to adding voice, music, sound and graphics
Introduction -- Day 1. Writing your first program -- Day 2. Properties and controls -- Day 3. Programming building blocks -- Day 4. The mouse -- Day 5. Menus -- Day 6. Dialog boxes -- Day 7. Graphics controls -- Day 8. Graphics methods -- Day 9. The grid control -- Day 10. Displaying and printing -- Day 11. Interfacing with Windows --Day 12. The keyboard -- Day 13. File-system controls -- Day 14. Accessing files -- Day 15. Arrays, OLE, and other topics -- Day 16. The data control and SQL -- Day 17. Multiple-document interface -- Day 18. Sending keystrokes, the spin control and the switch control -- Day 19. Sound programming -- Day 20. Sprite animation, WinG, and 3D virtual reality -- Day 21. Multimedia -- Appendix: Adding your own custom property to a form -- Index.
Includes index.
Keywords: MICROSOFT VISUAL BASIC